Three new Geogarypidae (Pseudoscorpiones: Garypoidea) from South Africa, with an updated key to the country’s geogarypid species - Neethling, J.a. (Zootaxa, 2024)
Two new species of Afrogarypus Beier, 1931, A. haddadi sp. nov. and A. pseudotriangularis sp. nov., and a new species of Geogarypus Chamberlin, 1930, G. grandis sp. nov. are described. Afrogarypus haddadi sp. nov. is diagnosed by a reduced isb and five rami on the female galea. Afrogarypus pseudotriangularis sp. nov. is diagnosed by trichobothria eb, esb, ib, est, isb, b, sb and st grouping within the first half of the fixed finger length and ten rami on the female galea. Geogarypus grandis sp. nov. is unique from the rest of its South African conspecifics in having two additional basal setae on the cheliceral hand, pedipalps densely ornamented with distinct protuberances and a unique protuberance at the base of the movable chelal finger. An updated identification key to the Geogarypidae species of South Africa is also presented.